The morality play as prelude to Elizabethan drama - Oosthuizen, Ann (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1966)
Although it is generally accepted that the Morality Plays greatly influenced Elizabethan drama, this statement is often followed by the rider that they are dull and lifeless and that their chief legacy is a sense of moral earnestness which also characterises the best Elizabethan drama. The aim of this thesis has been to read the Morality Plays closely and in an appreciative spirit in order to find out what significant contribution they do make to the techniques of Elizabethan drama and to a proper understanding of it. Chapter I discusses the earliest complete Morality, The Castle of Perseverance, which is the longest and most comprehensive of all the Moralities. The chapter tries to show what a Morality is about and how it differs from the great mediaeval cyclus, the Mystery Plays. It is also an attempt to relate the early Morality Play to other mediaeval literature and to show that it is closely linked to the homeletic literature of the period. Chapter II is a study of three Moralities of the period 1500- 1520. There are fewer Moralities in this period and the plays chosen show a marked similarity to The Castle of Perserverance in their structure, although they differ from the earlier Moralities in their attitude to their subject matter and in their portrayal of the different allegorical characters. The plays under discussion are Nature, Mundus et Infans and Magnyfycence Chapter III; the period after 1535 was a period of great political and religious upheaval and this chapter discusses the plays written for propaganda purposes in the strife between Catholic and Protestant. John Bale's Three Laws, an anti-Catholic play, was chosen because Bale is a startlingly original dramatist who makes use of techniques derived from the liturgy and from emblematic devices, and because he tries to mould the Mystery Plays and the History Plays into a Morality framework. The other plays The Conflict of Conscience was chosen because of its affinity to Dr Faustus and also because it tries to show the psychomachia in psychological, personal terms rather than in a general allegorical manner. Chapter IV discusses three later Moralities, Cambyses, Horestes and Appius Virginia, which portray historical or fictional characters in situations of conflict. They were chosen because they seem to show that the Morality Plays laid the bases for the Elizabethan tragic situation and the Elizabethan tragic hero. With such diverse material, it is difficult to trace a clear line of development from one play to the next, but each group of plays has its own contribution to make to our understanding of Elizabethan drama.
Keywords: Moralities, English; English drama -- Early modern and Elizabethan, 1500-1600 -- Classical influences